Pregnancy and COVID-19: Gestational profile of patients infected with SARS-Cov-2 - Silva, Ana Caroline Cardozo; Antunes, Camilla Emanuelle Neves; Pires, Cássia Pérola dos Anjos Braga; Vilela, Mateus Andrade; Pereira, Matheus Mendes (Seven Editora, 2023)
COVID-19 presents clinical manifestations from asymptomatic cases to deaths and causes vulnerability among several groups, pregnant women being one of them. Complications were related, as well as fetal death that seems to be associated with contamination by sars-cov-2. Method: this was a descriptive study of the case series type, which aims to identify the probability of occurrence of a disease or the clinical circumstance or the event that is the subject of the research. The data obtained after applying the semi-structured questionnaire to 61 out of a total of 132 pregnant women were descriptively tabulated and analyzed using a statistical program. Results: 53% of pregnant women had health conditions related to pregnancy: systemic arterial hypertension, diabetes mellitus, placenta previa, urinary tract infection, and placental displacement, among others. At the end of the pregnancy, 88.5% of the deliveries were full-term, 3.3% were premature and 8.2% did not complete the pregnancy due to miscarriage or fetal death. It was also found that the percentage of death was 2.3%. Conclusion: it was observed that the vast majority of the public interviewed in this study did not have clinical complications after infection with covid-19. The gestational outcome came to term, but a small group had maternal and perinatal sequelae. DOI:https://doi.org/10.56238/emerrelcovid19-036